Lady and the Tramp - Luske, Hamilton S.; Geronimi, Clyde; Jackson, Wilfred; Penner, Erdman; Rinaldi, Joe.; Wright, Ralph; DaGradi, Don.; Greene, Ward, 1892-; Lee, Peggy, 1920-2002.; Luddy, Barbara; Thompson, Bill, 1913-1971.; Roberts, Larry; et al. (Burbank, Calif. : Walt Disney Home Video ; Distributed by Buena Vista Home Entertainment ; DVS Home Video, 1998)
The story of Lady, a cocker spaniel, and her romantic adventures with Tramp, her mongrel friend. Animated.
VHS format.
Hi-Fi stereo ; Dolby surround.
Closed captioned for the hearing impaired.
Title on videocassette: Walt Disney's masterpiece Lady and the Tramp.
From the story by Ward Greene.
Originally released as a motion picture in 1955.
Keywords: Feature films; Children's films; Animated films; Films for the hearing impaired